2020
DOI: 10.1002/jor.24603
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage subtype and cytokine expression characterization during the acute inflammatory phase of mouse bone fracture repair

Abstract: Fracture repair is a complex process requiring heterotypic interactions between osteogenic cells and immune cells. Recent evidence indicates that macrophages are critically involved in fracture repair. Polarized macrophage populations differentially promote and regulate inflammation in other tissues, but little is known about the various macrophage subtypes and their signaling activities following a bone fracture. The authors hypothesized that classically activated (M1 subtype) and alternatively activated (M2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 37 publications
1
32
1
Order By: Relevance
“…It is well documented in the literature that M1 and M2 synergistically participate in the healing response after musculoskeletal injury. Considering HO to be a result of aberrant healing, we also found that both M1 and M2 infiltrated the regenerated tissue at the early stage after tendon injury, similar to what was observed during the repair process of muscle injury and bone fracture (59). However, quercetin prominently inhibited macrophage polarization to either the M1 or M2 subtype both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 80%
“…It is well documented in the literature that M1 and M2 synergistically participate in the healing response after musculoskeletal injury. Considering HO to be a result of aberrant healing, we also found that both M1 and M2 infiltrated the regenerated tissue at the early stage after tendon injury, similar to what was observed during the repair process of muscle injury and bone fracture (59). However, quercetin prominently inhibited macrophage polarization to either the M1 or M2 subtype both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 80%
“…MacCauley et al recently reported that the percentage of M1 macrophages is elevated seven days after femoral fractures in mice [ 40 ], although the number of macrophages and expressions of macrophage-related genes other than TNF- α at the damaged site were not altered four days after femoral injury in our study. These differences might be due to the differences of time course for bone repair after bone injury between fracture model and pinhole bone defect method in mice, since bone repair after fracture slowly progresses in general, compared to that after pinhole bone defect.…”
Section: Discussioncontrasting
confidence: 81%
“…The Th1 response requires high levels of inflammation and causes a strong cell-mediated immune response [20]. The Th1 response is important to macrophage activation, which is essential to fracture repair [21]. We hypothesize that a reduction in Th1 signaling activity in T2DM could reduce available macrophages at the fracture site contributing to impaired fracture repair.…”
Section: Expression Of Pro-inflammatory Mediators Il1-β and Tnf-α Are Significantly Inhibited In T2dmmentioning
confidence: 99%